2008
DOI: 10.1521/psyc.2008.71.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic/Racial Diversity and Posttraumatic Distress in the Acute Care Medical Setting

Abstract: Recent commentary has advocated for epidemiological investigation as a foundational science for understanding disparities in the delivery of mental health care and for the development of early trauma-focused interventions. Few acute care investigations have examined the diversity of ethnic/racial heritages or compared variations in early posttraumatic distress in representative samples of injured trauma survivors. Hospitalized injury survivors at two United States level I trauma centers were randomly approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…[21] The HTQ has been shown to produce reliable results in different languages [22] and has also been used and validated in many countries, including developing and poor countries. [23] It contains 16 of the 17 DSM-IV PTSD criteria and asks the respondent to endorse them on a scale of 0-4 (none, a little, moderate, quite a bit, extremely). We determined if an individual met symptom criteria for the occurrence of PTSD according to a scoring algorithm proposed by the Harvard Refugee Trauma Group on the basis of DSM-IV diagnostic criteria.…”
Section: Instrumentsmentioning
confidence: 99%
“…[21] The HTQ has been shown to produce reliable results in different languages [22] and has also been used and validated in many countries, including developing and poor countries. [23] It contains 16 of the 17 DSM-IV PTSD criteria and asks the respondent to endorse them on a scale of 0-4 (none, a little, moderate, quite a bit, extremely). We determined if an individual met symptom criteria for the occurrence of PTSD according to a scoring algorithm proposed by the Harvard Refugee Trauma Group on the basis of DSM-IV diagnostic criteria.…”
Section: Instrumentsmentioning
confidence: 99%
“…One recent nationwide prospective cohort study reports that approximately 30% of injured trauma survivors admitted to urban trauma centers have no insurance and approximately 40% report family household incomes of less than $30,000 per year (Zatzick et al, 2007). These patients are also highly racially and ethnically diverse: Previous clinical epidemiological investigations found that approximately 1 in 10 randomly sampled injured trauma survivors were monolingual, non–English speaking, with over 40 languages spoken in the cohort (Santos et al, 2008; Stephens et al, 2010). …”
Section: Intervention Inroads: a Case Example From Acute Care Medicalmentioning
confidence: 99%
“…5 Similarly, among 269 trauma patients hospitalized at 2 level 1 trauma centers in the Western region of the US, PTSD and related symptoms were significantly more frequent among Native patients than among white patients. 6 In the largest epidemiologic survey available regarding Native health, researchers found that two-thirds of the Native populations reported levels of lifetime trauma exposure that were higher than those in the general US population. 7 Additionally, trauma from unintentional injury, such as motor vehicle accidents, is experienced at higher rates by North American indigenous populations than by other ethnoracial groups (Dedra Buchwald, MD, personal communication; 2012).…”
Section: Introductionmentioning
confidence: 99%